Essential Japanese guidelines for the prevention of perioperative infections in the urological field: 2015 edition. (16th August 2016) - Yamamoto, Shingo; Shigemura, Katsumi; Kiyota, Hiroshi; Wada, Koichiro; Hayami, Hiroshi; Yasuda, Mitsuru; Takahashi, Satoshi; Ishikawa, Kiyohito; Hamasuna, Ryoichi; Arakawa, Soichi; Matsumoto, Tetsuro; ,
Abstract: After publication of the initial version of the Japanese guidelines for urological surgery in 2007, new surgical techniques have been introduced. Furthermore, several important issues, such as criteria for use of single‐dose antimicrobial prophylaxis and control of hospitalized infection, were also established, which led to alterations of the methods used for antimicrobial prophylaxis as well as perioperative management. The purpose of antimicrobial prophylaxis is to protect the surgical wound from contamination by normal bacterial flora. Antimicrobial prophylaxis should be based on penicillins with beta‐lactamase inhibitors, or first‐ or second‐generation cephalosporins, though penicillins without beta‐lactamase inhibitors should not be prescribed because of the high prevalence of antimicrobial resistance. As an adequate intratissue concentration of the antimicrobial at the surgical site should be accomplished by the time of initiation of surgery, antimicrobial prophylaxis should be started up to 30 min before beginning the operation. Antimicrobial prophylaxis should be terminated within 24 h in clean and clean‐contaminated surgery, and within 2 days of surgery using the bowels, because a longer duration is a risk factor for surgical site infection development. Importantly, possible risk factors for surgical site infections include the antimicrobial prophylaxis methodology used as well as others, such as duration of preoperative hospitalization, hand washing, the American Society of Anesthesiologists score, diabetes and smoking history. These guidelines are to be applied only for preoperatively non‐infected low‐risk patients. In cases with preoperative infection or bacteriuria that can cause a surgical site infection or urinary tract infection after surgery, patients must receive adequate preoperative treatment based on the individual situation.